2006
DOI: 10.1128/jcm.02397-05
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Dogs in Japan for Group 2 Canine Coronavirus Infection

Abstract: Specimens obtained from 96 dogs with respiratory and enteric clinical signs in Japan were retrospectively examined for group 2 coronavirus by reverse transcription-PCR. Two dogs were found to be positive. Phylogenetic analysis of the spike gene indicated that they were most probably related to the canine respiratory coronavirus recently described in the United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 17 publications
2
44
0
Order By: Relevance
“…Group 2 CRCoV, recently isolated in England as a new ITB pathogen closely related to bovine coronavirus [20], was again found to be associated with the diseased puppy in the present study. CRCoV infection was already confirmed in Japanese domestic dogs both seroepidemiologically [26] and molecular epidemiologically [43]. The present No.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Group 2 CRCoV, recently isolated in England as a new ITB pathogen closely related to bovine coronavirus [20], was again found to be associated with the diseased puppy in the present study. CRCoV infection was already confirmed in Japanese domestic dogs both seroepidemiologically [26] and molecular epidemiologically [43]. The present No.…”
Section: Discussionsupporting
confidence: 61%
“…Group 1 CCoV was detected by the Taq Man PCR assay described by Gut et al [23]. Group 2 CRCoV was detected by the RT-PCR assay that targets the hemagglutinin-esterase gene of group 2 coronavirus by the methods described recently [43].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also reported that the known group 1 coronaviruses (CCoV) that cause enteritis and an unknown group 2 coronavirus were prevalent in domestic dogs in Japan [8]. Compatible results in a survey of dogs in Japan for group 2 canine coronavirus infection were also reported by Yachi and Mochizuki [18].…”
mentioning
confidence: 57%
“…CRCoV is a novel pathogen detected in the respiratory tract of dogs suffering from severe respiratory disease but itself is thought only to be associated with subclinical or asymptomatic disease [7]. To date, few CRCoV strains have been isolated from a small number of countries: the United Kingdom (n=2), Japan (n=2), Italy (n=1), and Korea (n=3) [1,6,12,17]. Antibodies against CRCoV are common in canine populations in the United Kingdom (36.2%), Republic of Ireland (30.3%), USA (54.7%), Japan (17.8%), Italy (32.1%), and New Zealand (29%) [4,9,10,13].…”
mentioning
confidence: 99%